Multi-levels bargaining and efficiency in search economies - Olivier L'Haridon; Franck Malherbet (Institute for the Study of Labor (IZA), 2006)
In this note, we extend the traditional search and matching framework to take account of the different levels at which negotiations take place. We show that, in the absence of any distortion, sector-level bargaining ought to be less efficient than bargaining taking place at the other levels. It follows that the introduction of labor market policies as a combination of employment protection, hiring subsidy and payroll tax improves efficiency. This result suggests that the relationship between the level at which bargaining takes place and the labor market performance is far more conditional than most studies acknowledge.
urn:nbn:de:101:1-2009031384
Keywords: 330